Modification of SnO2 Nanowires with TeO2 Branches and Their Enhanced Gas Sensing - Myung Sik Choi; Jae Hoon Bang; Ali Mirzaei; Hyoun Woo Kim; Sang Sub Kim (Proceedings, 2017)
We prepared a highly sensitive and selective NO2 sensor, based on the TeO2 branched SnO2 nanowires (NWs), in terms of vapor-liquid-solid method, with subsequent growing of branches on the stems of SnO2 NWs. Fabricated sensors showed a high response higher than 10 to 10 ppm of NO2 gas at 100 °C. We investigated the associated sensing mechanisms, with respect to the enhancement of sensing behaviors by the addition of TeO2 branches. Based on the results obtained in this work, we believe that the present sensor with an efficient fabrication technique, and high sensitivity and selectivity can be used for detection of NO2 gas in real applications.